Analog Network Coding for chain topology in non-mutual transmission - Saleh V.; Rusli M.E.; Ahmed S.K.; Mohamad H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Analytical models; Chains; Codes (symbols); Topology; Analog network coding; Analog network coding (ANC); Analytical approach; Network simulation; Number of transmissions; Performance parameters; Traditional approaches; Wireless transmissions; Network coding